Survival Analysis and Risk Factors for COVID-19 Patients at Koja Hospital - Kemal Pradana Putra; Dian Ratih L; Hesty Utami R; Rita Novariani; Natasja R Kandou (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2024)
The COVID-19 pandemic impacts global health, and no specific drug has proven effective in curing SARS-CoV-2 infection. This study aimed to analyze the survival characteristics of COVID-19 patients in Koja Hospital. This research method is analytically observational with a cross-sectional design. The study population was 1080, and the research sample was 284 patients. The sampling used a purposive sampling method with a retrospective approach from the medical records of confirmed COVID-19 inpatients from May to October 2020. The analysis uses SPSS software version 26. Categorical variables were analyzed using the chi-square test or Fisher’s exact test. Kaplan Meier, Log Rank, and Cox Regression were used for the probability of survival analysis and mortality risk ratio in COVID-19 patients. The case fatality rate (CFR) of 284 COVID-19 patients was 20.4%. The mean age of the patients was 49 years (IQR 37–57). The most common comorbidity was hypertension, 34%. The average probability of survival of COVID-19 patients was above 60%. In addition to gender, predictors including age, comorbidities, type of intensive care, and use of antivirals had significant differences and affected the chances of survival of COVID-19 patients. Patients given oseltamivir monotherapy had the highest survival rate of about 80% after undergoing treatment for about 38 days (p equal 0.000). The mortality risk ratio of COVID-19 patients with comorbid diabetes mellitus was 8.7 times higher than that of those without comorbidities (95% CI 1,02–75.82, p less than 0.048). Patients with intensive care had an 11.43 times increased mortality risk ratio compared to usual care (95% CI 6,34–20,62, p less than 0.000). The conclusion of this study is intensive care and a history of diabetes mellitus are associated with the risk of death. There needs to be an increase in COVID-19 control measures, especially in populations prone to comorbid diabetes with severe and critical degrees.